Kinetics and characterization of extracellular vesicle release from cells infected with a clinical isolate of respiratory syncytial virus A (ON1 genotype) - Matteo Fracella; Valeria Manganelli; Alessandra Pierangeli; Carolina Scagnolari; Manuel Pacchiele; Eleonora Coratti; Roberta Campagna; Gloria Riitano; Federica Fratini; Agostina Longo; Maurizio Sorice; Guido Antonelli (Medical Microbiology and Immunology, 2026)
Despite the recent approval of preventive measures, the disease burden of respiratory syncytial virus (RSV) infection in children and older adults remains significant. To improve understanding of RSV disease, this study characterized extracellular microvesicles (EMVs) secreted during in vitro infection with a clinical RSV-A (ON1 genotype) strain (RSV/40G-A), isolated in 2022 from a pediatric pneumonia case. The type and content of EMVs released by A549 and BEAS-2B respiratory epithelial cells infected with this clinical isolate were analyzed up to 96 h post-infection (hpi). RSV infection induced a time-dependent increase in EMV levels compared to uninfected controls. EMVs released by infected BEAS-2B and A549 cells contained increasing levels of RSV nucleocapsid protein (RSV-NP) and viral RNA with a peak at 72 hpi. These findings suggest that the kinetics of vesicular release and EMV content are modulated during RSV infection. EMV secretion by host cells may constitute a potential mechanism for intercellular communication or immune activation.